PENGGUNAAN METODE EKSPOSITORI PADA MATA PELAJARAN PAK DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI SD INPRES PONDANG - Koloy, Olfie D. (Tumou Tou, 2020)
In the learning process that involves material, methods, media props and so on must also experience changes towards renewal (innovation). Based on the problems seen, it is related to the improvement of Christian learning achievement by applying expository teaching models to grade VI students of SD Inpres Pondang. The purpose of this study in order to determine the increase in Christian learning achievement after applying expository teaching model. In this study using action research and data obtained from formative tests, observation sheets of teaching, and learning activities of students. The results of the study found that student achievement has increased from cycle I (51%) to cycle II (89%). Through this research, it can be said that the expository teaching model can positively influence achievement, interest, attention, and participation, learning motivation of SD Inpres Pondang students, and this learning model can be used as alternative learning of Protestant Christianity.